Effectiveness of food-based fortification in older people a systematic review and meta-analysis - Morilla-Herrera, Juan Carlos; Martín-Santos, Francisco Javier; Caro-Bautista, Jorge; Saucedo Figueredo, María del Carmen; García-Mayor, Silvia; Morales-Asencio, José Miguel (Elsevier, 2016)
Abstract: Background: Early intervention with nutritional support has been found to stop weight loss in older people malnourished or at risk of malnutrition. Enriched food could be a more attractive alternative to improve meals, than conventional oral nutritional supplements. Aims: To determine the effectiveness of foodbased fortification to prevent risk of malnutrition in elderly patients in community or institutionalized elderly patients. Methods: A systematic review was conducted of randomized controlled trials, quasi-experimental, and interrupted time series including a longitudinal analysis. Participants: Elderly patients who are institutionalized, hospitalized or community-dwelling, with a minimum average age of 65 years. Intervention: Studies had to compare food-based fortification against alternatives. Studies that used oral nutritional supplementation such as commercial sip feeds, vitamin or mineral supplements were excluded. The search was conducted in Cochrane, CINAHL, PubMed, EMBASE, LILACS, and Cuiden. An independent peer review was carried out. Results: From 1011 studies obtained, 7 were included for the systematic review, with 588 participants. It was possible to perform meta-analysis of four studies that provided results on caloric and protein intake. Food-based fortification yielded positive results in the total amount of ingested calories and protein. Nevertheless, due to the small number of participants and the poor quality of some studies, further high quality studies are required to provide reliable evidence. Implications for practice: Despite the limited evidence, due to their simplicity, low cost, and positive results in protein and calories intake, simple dietary interventions based on the food-based fortification or densification with protein or energy of the standard diet could be considered in patients at risk of malnutrition.
Keywords: Ancianos - Alimentación; Necesidades nutricionales; Food; Systematic review; Older people; Nutrition